Macroevolutionary pattern of sexual size dimorphism in geckos corresponds to intraspecific temperature-induced variation - Starostová, Z; Kubicka, L; Kratochvíl, L (Journal of evolutionary biology, 2010)
Many animal lineages exhibit allometry in sexual size dimorphism (SSD), known as 'Rensch's rule'. When applied to the interspecific level, this rule states that males are more evolutionary plastic in body size than females and that male-biased SSD increases with body size. One of the explanations for the occurrence of Rensch's rule is the differential-plasticity hypothesis assuming that higher evolutionary plasticity in males is a consequence of larger sensitivity of male growth to environmental cues. We have confirmed the pattern consistent with Rensch's rule among species of the gecko genus Paroedura and followed the ontogeny of SSD at three constant temperatures in a male-larger species (Paroedura picta). In this species, males exhibited larger temperature-induced phenotypic plasticity in final body size than females, and body size and SSD correlated across temperatures. This result supports the differential-plasticity hypothesis and points to the role phenotypic plasticity plays in generating of evolutionary novelties.
Keywords: ženské pohlaví; Species Specificity; ještěři; Female; druhová specificita; Animals; Biological Evolution; Male; velikost těla; Body Size; pohlavní dimorfismus; teplota; mužské pohlaví; biologická evoluce; Lizards; Sex Characteristics; zvířata; Temperature